KARAKTERISTIK SOSIAL EKONOMI YANG MEMPENGARUHI LITERASI KEUANGAN SERTA DAMPAKNYA TERHADAP MANAJEMEN KEUANGAN PERSONAL (Survei Pada Pegawai Negeri Sipil Daerah di Kabupaten Kuningan) - Wiharno, Herma (Program Studi Akuntansi, Universitas Kuningan, 2015)
The purpose of this study was to assess the socioeconomic characteristics that influence financial literacy and the influence of financial literacy towards personal financial management. The financial literacy in this study was divided into dimensions of financial literacy, financial behavior, and financial attitudes.The method used is descriptive and verificative methods. This research was conducted in the Kuningan Regency, and the Regional Civil Servants were the units of analysis. The samples used in this study were 390 Regional Civil Servants with the sample collection technique of proportional stratified cluster random sampling.The results of the verificative analysis revealed that only education levels significantly affect the financial knowledge, while having a significant effect on the behavior and attitudes in addition to the level of financial education is also a place to stay. Financial knowledge, financial behaviors, and financial attitudes significantly influence towards the personal financial management. In relation between socioeconomic characteristics with personal financial management, education level only that significant effect on personal financial management.